PERAN KEPALA SUKU DALAM SISTEM NOKEN PADA PEMILUKADA DI DISTRIK KAMU KABUPATEN DOGIYAI PROVINSI PAPUA TAHUN 2013 - Tarima, Yerianto; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2016)
ABSTRACT The enforcement of general election in Papua province especially in mountainous area in Papua still uses Noken system. A chieftain has an important role in making decision. The important role of a chieftain is not only in the tradition order but also in the country government system. The purpose of this study is to know the role of a chieftain in Noken system from the general election in Kamu District Dogiyai Regency of Papua Province 2013. This research used qualitative method and descriptive approach. The data source is primary and secondary data. The primary data was taken from the direct interview and documentation of the informant. The secondary data was collected by using the formal scripts inscriptive. The determination of informant is done by making the informant matrix table. The technique of data collection is by doing interview with the selected informant deeply and by collected the documents which have connection with this research. The result of this study is found that Kamu District in Dogiyai regency still uses Noken system in general election process. The system is hang system or string system where they still consider to deliberation process. The role of a chieftain is decision making in Noken system. The role of a chieftain is a social role and does not bound with the formal law in a country. The loyalty of the community based on the loyalty to chieftain. Based on the result, the roles of chieftain in Noken system are firstly, summon the people to give instruction about the general election process. Secondly, explain about candidate’s vision and mission. Thirdly, control the entry process of ballot as the result of the togetherness agreement into the Noken. Fourthly, bring and give the result of ballot to the organizing committee. The result of this research also found the negative impact of the chieftain role. The negative impact of the chieftain role is the greasing the palm happening where was done by the candidates. These candidates used the authority of the chieftain in making decision. Key word: the role of chieftain, Noken System, the general election of the region chief 2013,                          Dogiyai Regency